Low density lipoprotein detection based on antibody immobilized self-assembled monolayer: Investigations of kinetic and thermodynamic properties - Matharu Z.; Bandodkar A.J.; Sumana G.; Solanki P.R.; Mala Ekanayake E.M.I.; Kaneto K.; Gupta V.; Malhotra B.D. (My University, 2025)
Human plasma low density lipoprotein (LDL) immunosensor based on surface plasmon resonance (SPR) and quartz crystal microbalance (QCM) was fabricated by immobilizing antiapolipoprotein B (AAB) onto selfassembled monolayer (SAM) of 4-aminothiophenol (ATP). The AAB/ATP/Au immunosensor can detect LDL up to 0.252 μM (84 mg/dL) and 0.360 μm(120 mg/dL) with QCM and SPR, respectively. The SPR and QCM measurements were further utilized to study the reaction kinetics of the AAB-LDL interaction. The adsorption process involved was explored using Langmuir adsorption isotherm and Freundlich adsorption models. The thermodynamic parameters such as change in Gibb's free energy (δGads), change in enthalpy (Afluis), and change in entropy (δSads) determined at 283, 298, and 308 K revealed that the AAB-LDL interaction is endothermic in nature and is governed by entropy. Kinetic, thermodynamic, and sticking probability studies disclosed that desorption of the water molecules from the active sites of AAB and LDL plays a key role in the interaction process and increase in temperature favors binding of LDL with the AAB/ ATP/Au immunosensor. Thus, the studies were utilized to unravel the most important subprocess involved in the adsorption of LDL onto AAB-modified ATP/Au surface that may help in the fabrication of LDL immunosensors with better efficiency. © 2009 American Chemical Society.